1962
DOI: 10.1111/j.1469-7998.1962.tb05684.x
|View full text |Cite
|
Sign up to set email alerts
|

COMMUNICATION BY POSTURES AND FACIAL EXPRESSIONS IN THE RHESUS MONKEY (MACACA MULATTA)

Abstract: The principal postures and facial expressions used by the rhesus monkey in social communication are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
1

Year Published

1977
1977
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(119 citation statements)
references
References 7 publications
5
113
1
Order By: Relevance
“…Direct gaze is an aversive, threatening signal for rhesus monkeys [73,74], so in order to study the development of gaze avoidance, Mendelson [10] implanted newborn rhesus monkeys with sclera coils that provide the ability to accurately measure viewing duration. At one, three and seven weeks of age, monkeys were shown conspecific's faces with their gaze either slightly averted, or direct.…”
Section: Part 1 (A) Configural Information In Facesmentioning
confidence: 99%
“…Direct gaze is an aversive, threatening signal for rhesus monkeys [73,74], so in order to study the development of gaze avoidance, Mendelson [10] implanted newborn rhesus monkeys with sclera coils that provide the ability to accurately measure viewing duration. At one, three and seven weeks of age, monkeys were shown conspecific's faces with their gaze either slightly averted, or direct.…”
Section: Part 1 (A) Configural Information In Facesmentioning
confidence: 99%
“…The communicative function of facial displays has been investigated primarily in Old World primate species, namely macaques and chimpanzees [Hinde and Rowell, 1962;van Hooff, 1967van Hooff, , 1972Chevalier-Skolnikoff, 1973, 1982Redican, 1975;Preuschoft, 1995;van Hooff, 1995a, 1997;de Waal, 2003]. The very few studies focused on the ontogeny of facial displays (see Chevalier-Skolnikoff [1974] for Macaca arctoides and Plooij [1984] for Pan troglodytes ) have shown that in macaques and chimpanzees facial displays develop gradually, changing in shape and often in function from the infant to the adult forms (see Maestripieri and Call [1996] for a review).…”
Section: Introductionmentioning
confidence: 99%
“…However, because PI did not escape from their sight and just crouched in open areas, without exhibiting any submissive or reconciliatory behavior toward his attackers, the troop males did not recognize the end of the conflict [Hinde and Rowell, 1962;Maestripieri and Wallen, 1997].…”
Section: Length Of Conflict and Crouching Posture Of The Victimmentioning
confidence: 97%